Systematic genetic analyses of GWAS data reveal an association between the immune system and insomnia. Issue 7 (15th May 2019) - Xiang, Bo; Liu, Kezhi; Yu, Minglan; Liang, Xuemei; Huang, Chaohua; Zhang, Jin; He, Wenying; Lei, Wei; Chen, Jing; Gu, Xiaochu; Gong, Ke
Abstract: Background: Previous studies have inferred a strong genetic component for insomnia. However, the etiology of insomnia is still unclear. The aim of the current study was to explore potential biological pathways, gene networks, and brain regions associated with insomnia. Methods: Using pathways (gene sets) from Reactome, we carried out a two‐stage gene set enrichment analysis strategy. From a large genome‐wide association studies (GWASs) of insomnia symptoms (32, 155 cases/26, 973 controls), significant gene sets were tested for replication in other large GWASs of insomnia complaints (32, 384 cases/80, 622 controls). After the network analysis of unique genes within the replicated pathways, a gene set analysis for genes in each cluster/module of the enhancing neuroimaging genetics through meta‐analysis GWAS data was performed for the volumes of the intracranial and seven subcortical regions. Results: A total of 31 of 1, 816 Reactome pathways were identified and showed associations with insomnia risk. In addition, seven functionally and topologically interconnected clusters (clusters 0–6) and six gene modules (named Yellow, Blue, Brown, Green, Red, and Turquoise) were associated with insomnia. Moreover, significant associations were detected between common variants of the genes in Cluster 2 with hippocampal volume ( p  = 0.035; family wise error [FWE] correction) and the red module with intracranial volume ( p  = 0.047; FWE correction). Functional enrichment for genes in the Cluster 2 and the Red module revealed the involvement of immune responses, nervous system development, NIK/NF‐kappaB signaling, and I‐kappaB kinase/NF‐kappaB signaling. Core genes ( UBC, UBB, and UBA52 ) in the interconnected functional network were found to be involved in regulating brain development. Conclusions: The current study demonstrates that the immune system and the hippocampus may play central roles in neurodevelopment and insomnia risk. Abstract : The association between the immune system and insomnia; UBC, UBB, and UBA52 participated in regulating brain development were associated with insomnia.